PENYELESAIAN MODEL DISTRIBUSI SUHU BUMI DI SEKITAR SUMUR PANAS BUMI DENGAN METODE KOEFISIEN TAK TENTU - Niswah, Lutfiyatun; ., Widowati; ., Djuwandi (MATEMATIKA, 2014)
Mathematical model in this paper describes the formation temperature distribution related to the process of heat transfer in geothermal wellbore. The model of formation temperature is based on the single thermal conduction equation. The form of the model is ordinary differential equation. Further, we derived an analytical solution with the method of undetermined coeffisient. The simulation is done to determine the model’s behavior based on the secondary data. Based on the simulation result is found that if the increasing depth hence the temperature increases.